ANALYSIS OF THE OBJECTIVE AND SUBJECTIVE ELEMENTS OF THE CRIME OF VIOLATING ADMINISTRATIVE SUPERVISION RULES (Uzbek Scholar Journal, 2026)
This article provides a comprehensive criminal-legal analysis of the crime under Article 226 of the Criminal Code of the Republic of Uzbekistan — violation of administrative supervision rules. The object, objective side, subject and subjective side of the crime are examined based on the scientific views of Uzbek and foreign legal scholars. The role of the administrative prejudice institution in the composition of this crime, the content of the concepts of “valid reasons” and “unauthorized departure”, as well as practical issues of proving the purpose of “evasion” are covered. The research results contribute to improving law enforcement practice.